PENGARUH PENAMBAHAN PROBIOTIK HERBAL PADA RANSUM TERHADAP PERFORMENT ITIK PEDAGING - Endah Subekti; Dewi Hastuti (MEDIAGRO, 2015)
The experiment was conducted to determine the effect of probiotics in diet on performance ( feed consumption, weight gain, and feed conversion) of ducks. Two  hundred  of  day  old  ducks  were  divided  into  five  dietary  treatments.  Each treatment was replicated four times with ten ducks per replicate. The five dietary treatments  were  P0  (diet  without  the  addition  of  probiotics),  P1  (diet  plus probiotics  5  ml/l),  P2  (diet  plus  probiotics  10  ml/l),  P3  (diet  plus  probiotics  15 ml/l) and  P4 (diet plus probiotics 20 ml/l). Five dietary treatments and drinking water  were  given  ad  libitum.  The  collected  data  were  analysed  using  analysis variance  of  completely  randomized  design  and  continued  by  Duncan’s  New Multiple  Range  Test  if  analysis  of  the  variance  indicated  significant  difference. The  result  showed  that  addition  of  probiotic  levels  in  diet  on  duck  was significantly different on weight gain and feed conversion ratio of duck. Diet with probiotic  15  ml/l  (P3)  resulted  good  performance  of  duck.  It  gave  an  average weight of 1,366 g, 2.07 feed conversion and feed consumtion 2,829 for six weeks.Keywords: Duck, Probiotic, Performance.